2020
DOI: 10.1111/jgs.16640
|View full text |Cite
|
Sign up to set email alerts
|

Safer Prescribing for Hospitalized Older Adults with an Electronic Health Records‐Based Prescribing Context

Abstract: BACKGROUND/OBJECTIVES Hospitalized older adults are at risk of receiving potentially inappropriate medication (PIM) doses, driven in part by age‐independent dose defaults used by electronic health records (EHRs), leading providers to prescribe for older adults as they do for younger adults. We studied whether an automated EHR‐based medication support tool would reduce PIM dosing for hospitalized older adults. DESIGN Pre‐post study design. SETTING Tertiary care, level 1 trauma, academic medical center in Oregon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Analysis of the GPC has shown 10–30% increases in age-appropriate orders for the 10 most commonly used medications across drug classes that translated to reductions in total daily doses and average dose strengths received by older patients. These results suggest that the GPC is a feasible method to improve safe prescribing for hospitalized older adults (Drago et al, 2020).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Analysis of the GPC has shown 10–30% increases in age-appropriate orders for the 10 most commonly used medications across drug classes that translated to reductions in total daily doses and average dose strengths received by older patients. These results suggest that the GPC is a feasible method to improve safe prescribing for hospitalized older adults (Drago et al, 2020).…”
mentioning
confidence: 90%
“…The GPC better aligns prescribing practice with recommendations for older adults and an important part of the design process was to avoid hard stop alerts. The initial investigation into the GPC’s impact focused on orders and actual doses received by patients but little was known about its impact on computerized prescribing and order verification experiences for end users (Drago et al, 2020). This study aimed to describe the GPC’s reported impact on usual electronic prescribing workflows and user experiences among our inpatient providers and pharmacists in both community and academic settings.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Our health system developed and embedded the Geriatric Prescribing Context (GPC) into the EHR in July 2017. 9 The GPC is an automated set of age-friendly default doses and frequencies triggered when prescribers write orders for patients 75 years and older admitted to the hospital or emergency department. There are no hard stops, alerts or extra steps prescribers have to take to write medication orders.…”
Section: Introductionmentioning
confidence: 99%
“…Initial investigation demonstrated 10%–30% improvement in the number of medication orders using the age-friendly defaults in the top 10 most commonly used inpatient medications adjusted by the GPC. 9 Little is yet known about the effect of the GPC on ADEs as this is a novel adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…3 EHR default doses are often higher than recommended for older adults. 4 Studies by Peterson et al, 2005 5 and Drago et al, 2020 6 have shown that computerized provider order entry (CPOE) defaults can increase safe prescribing. Literature exploring defaults' effectiveness in decreasing IP has largely occurred in non-Hispanic White adults.…”
Section: Introductionmentioning
confidence: 99%